Low-temperature plasma-assisted two-dimensional nano material preparation process

Through the low-temperature plasma-assisted preparation process, selective peeling of MXene materials and the introduction of surface functional groups are achieved, structural damage and process environment problems caused by strong acid etching are solved, dispersion and stability of the materials are improved, and are suitable for electrochemical energy storage, catalysis and other fields.

CN120270998AInactive Publication Date: 2025-07-08BEIJING NANO FRUIT TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510613247.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-13
Publication Date
2025-07-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing MXene preparation method, strong acid etching leads to easy damage to the material structure, difficult to introduce functional groups simultaneously, and unfriendly process environment, making it difficult to achieve green manufacturing and scale.

Method used

The low-temperature plasma-assisted preparation process is adopted, and the use of organic amine compounds, lithium salts and mixed solvents in a gas-liquid collaborative environment, combined with low-temperature radiofrequency plasma treatment is achieved to achieve selective peeling of layer A and form functional groups on the surface of the material to avoid the use of high temperature and strong acids.

Benefits of technology

Under mild conditions, the integrity of the MXene sheet structure and the synchronous control of surface functional groups is achieved, which improves the dispersion and electrochemical stability of the material, is highly adaptable, and is suitable for multiple application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120270998A_ABST
    Figure CN120270998A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of two-dimensional nano material preparation, and discloses a low-temperature plasma-assisted two-dimensional nano material preparation process, which comprises the following steps: firstly, dispersing an MAX phase material in a liquid phase containing organic amine, lithium salt and a mixed solvent to construct a precursor environment with reaction activity; then performing low-temperature treatment in a plasma atmosphere formed by ammonia gas and argon to realize directional stripping of the layer A and synchronous introduction of surface functional groups; then, through the steps of centrifugation and neutral washing, unreacted impurities and by-products are effectively removed, and the material purity is ensured; performing ultrasonic-assisted redispersion, and introducing an amine stabilizer to maintain the monodisperse state of the lamellar structure. Through the process, the MXene material with a complete structure and uniform surface modification can be efficiently obtained under a mild condition, the dispersity and the interface stability of the MXene material are improved, and compared with a traditional strong corrosion method, the reaction destructiveness and the environmental risk are remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of two-dimensional nanomaterial preparation, and specifically provides a process for preparing two-dimensional nanomaterials assisted by low-temperature plasma. Background Art

[0002] MXene is a class of two-dimensional transition metal carbides, nitrides or carbonitrides prepared by removing the A element layer (such as Al, Si, etc.) from the MAX phase precursor. In recent years, it has been widely studied in many fields such as energy storage, catalysis, separation and biological applications due to its excellent electrical conductivity, tunable surface chemistry and high specific surface area. The performance of MXene depends to a large extent on its exfoliation degree, layer uniformity and surface functional group structure. Therefore, the controllability and generality of its preparation method have always been the core problems in research and application.

[0003] Currently, the mainstream method for preparing MXene is still mainly the strong acid etching method, often using hydrofluoric acid (HF) or an in-situ HF system generated from fluorinated salts to selectively etch the MAX phase to remove the A layer. However, this type of method has multiple technical bottlenecks: First, the strong acid etching reaction is violent, and it is difficult to avoid non-selective corrosion of the M-X layer during the reaction, which easily causes damage to the sheet edges and structural degradation, thereby affecting its mechanical and electrochemical stability; Second, HF itself has extremely strong corrosiveness and toxicity, requiring high requirements for equipment materials and operation safety, and significantly increasing the packaging cost of the process environment, which is not conducive to green manufacturing and large-scale promotion. In addition, after traditional acid etching, secondary surface modification is often required to introduce target functional groups, with complex steps and low efficiency.

[0004] In recent years, there have also been attempts in the literature to use gas-phase plasma, solvothermal reactions, etc. to replace the acid etching route, but these methods still have problems such as harsh treatment conditions, poor reaction adaptability, and uncontrollable functional structures. For example, high-temperature plasma treatment in a single atmosphere easily leads to ablation of the material structure and lacks the ability to guide functional groups; without the introduction of additional excitation energy in the liquid phase system, it is difficult to substantially exfoliate the A layer without the aid of acidic conditions. Therefore, under the existing technical conditions, how to achieve precise removal of the A layer under mild conditions while controlling the integration of the MXene sheet structure integrity and surface functional group construction is the key technical problem faced in the field of MXene preparation. Summary of the Invention

[0005] Aiming at the deficiencies of the prior art, the present invention provides a process for preparing two-dimensional nanomaterials assisted by low-temperature plasma, which solves the problems in the existing MXene preparation that the exfoliation process depends on strong corrosion conditions, the structure is easily damaged, and functional groups are difficult to introduce synchronously.

[0006] To achieve the above object, the present invention is realized through the following technical solutions: A preparation process of two-dimensional nanomaterials assisted by low-temperature plasma, comprising the following steps: S1. Add the MAX phase precursor material into a liquid system composed of an organic amine compound, a lithium salt, and a mixed solvent, and perform a dispersion treatment to form a suspension slurry; S2. Under a gas-liquid synergistic environment, apply low-temperature plasma treatment to the slurry, so that the A layer in the MAX phase precursor is selectively peeled off and functional groups are formed on the material surface; S3. Centrifuge and wash the slurry after plasma treatment to obtain a dispersed two-dimensional nanomaterial; S4. Perform a redispersion treatment on the two-dimensional nanomaterial; S5. Freeze-dry and store the obtained material as needed.

[0007] Preferably, in step S1, the organic amine compound is isopropylamine, and its concentration is 0.005-0.02 mol / L. In step S1, the lithium salt is lithium hexafluorophosphate, and its concentration is 0.01-0.1 mol / L. In step S1, the mixed solvent is a mixed solution of deionized water and ethanol with a volume ratio of 5:5 to 7:3.

[0008] Preferably, in step S2, the low-temperature plasma is radio frequency plasma, the frequency is 13.56 MHz ± 1 MHz, the power is 20-60 W, and the treatment time is 10-30 min.

[0009] Preferably, in step S2, the low-temperature plasma treatment uses a mixed gas of argon and ammonia, the argon flow rate is 30-70 sccm, the ammonia flow rate is 1-5 sccm, and the volume ratio of the two is 93:7 to 97:3.

[0010] Preferably, in step S4, the redispersion treatment is carried out using an ultrasonic disperser, the ultrasonic frequency is 20-40 kHz, the treatment time is 20-60 min, and the ultrasonic power is 100-300 W.

[0011] Preferably, in step S3, the washing liquid for washing is deionized water with a pH value in the range of 6.5-7.5, and it is washed 3-5 times, and the volume of each single wash is 0.5-1 times that of the original system.

[0012] Preferably, when performing the redispersion treatment in step S4, isopropylamine needs to be added to the dispersion liquid formed by the two-dimensional nanomaterial as a stabilizer, and the volume fraction of the isopropylamine is 0.05-0.2% of the total volume of the dispersion liquid.

[0013] Preferably, in the step S5, the temperature control range for lyophilization is -60 to -40 °C, the vacuum degree is 5 - 20 Pa, and the drying time is 24 - 72 h.

[0014] Preferably, the material obtained in the step S5 is the final two-dimensional nanomaterial product, which includes the following components by mass fraction: Ti3C2-based two-dimensional sheet material: 85 - 95 parts; Surface-modified amino functional groups: 2 - 6 parts; The remaining soluble lithium salts and amine impurity residues: 1 - 5 parts.

[0015] Preferably, in the step S1, the MAX phase precursor material has the general formula M n+1 AX n , where M is one or more transition metals selected from Ti, V, Cr, Nb, Zr, Mo, A is one or more A elements selected from Al, Si, Ga, In, X is C or N or a combination thereof, n is 1 - 3, the added mass of the MAX phase precursor material is 1 - 5 wt% of the mass of the liquid system, and its particle size is 25 - 50 μm.

[0016] The present invention provides a preparation process for two-dimensional nanomaterials assisted by low-temperature plasma. It has the following beneficial effects: 1. By adopting the "plasma-chemical synergistic exfoliation" technical path and through the combined action of ammonia, lithium salts and low-temperature plasma, the present invention realizes the directional stripping and structure retention of the A layer in the MAX phase material, achieving the purpose of forming highly crystalline MXene under mild conditions. Different from the traditional strong acid etching method, this scheme avoids the risks of structure collapse and by-product deposition, and solves the problems of serious lattice damage and interlayer disorder in the prior art.

[0017] 2. By introducing amine small molecules to synergistically modify with ammonia and in-situ generating amino functional groups under the action of plasma, the present invention effectively improves the hydrophilicity and charge stability of the MXene surface, significantly enhances the material dispersibility, increases the Zeta potential, and the material does not settle for a long time. Compared with the methods in the prior art that rely on post-treatment or high-temperature gas-phase reactions for surface functionalization, it avoids the problems of structure damage and uneven functional groups, and improves the tunability of interface control.

[0018] 3. The present invention proposes a plasma excitation system with adjustment ability, which can realize the synchronous control of material structure and surface function at a specific energy density. This scheme has both processing stability and adaptability, and can be extended to different types of layered precursors. Compared with the traditional single atmosphere or fixed parameter processing methods, it solves the problems of poor material adaptability and narrow process window. Description of the Drawings

[0019] Figure 1 This is the process flow chart for the preparation of the present invention. Specific embodiments

[0020] Next, in conjunction with the accompanying drawings of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the scope of protection of the present invention.

[0021] Please refer to the appendix Figure 1 , the embodiments of the present invention provide a preparation process for two-dimensional nanomaterials assisted by low-temperature plasma, including the following steps: In the first step (S1) of the process, the present invention disperses the MAX-phase precursor material in a liquid system composed of organic amine compounds, lithium salts, and a mixed solvent to form a suspension slurry. The MAX-phase material itself has a layered structure, and its general formula is M n+1 AX n , where M is a transition metal element (such as Ti, V, Nb, etc.), A is an element of Group IIIA or IVA (such as Al, Si, etc.), X is carbon or nitrogen, and n is usually 1 to 3. The key to this structure is that the A layer can be selectively peeled off, thereby releasing a two-dimensional sheet structure composed of M-X bonds. By adding the MAX material to the mixed liquid system in a mass ratio of 1-5 wt% and controlling its particle size between 25-50 μm, not only is a sufficient reaction interface ensured, but also conditions for interface activation in the plasma treatment stage are provided. At the same time, the introduction of organic amines (such as isopropylamine) and lithium salts helps with the chemical activation of the A layer in the early stage, stabilizes the slurry system, avoids particle agglomeration, and improves the plasma reaction uniformity.

[0022] Entering step S2, the present invention introduces low-temperature radio-frequency plasma in a gas-liquid synergistic environment, and uses the high-energy particles and short-wave excitation light excited by the plasma to achieve directional energy input to specific atomic layers on the material surface. In particular, by controlling the plasma frequency (13.56 MHz ± 1 MHz), power (20-60 W), and treatment time (10-30 min), the cleavage of the A element layer (such as the Al layer) in the MAX phase can be effectively induced while avoiding damage to the M-X bond. The mixed use of argon and ammonia plays a synergistic effect here: argon provides a plasma excitation environment, while trace amounts of ammonia help introduce -NH2 functional groups to the surface of the nanosheets in the interfacial reaction, thereby improving subsequent dispersibility and surface activity. In addition, the low-temperature plasma treatment process keeps the system temperature at 30-60 °C, effectively avoiding the thermal damage problem caused by high temperatures, which is one of the important innovations of the present invention compared to traditional methods such as thermal exfoliation and strong acid etching.

[0023] Subsequently, in step S3, through centrifugal separation and multiple washings with deionized water, residual unreacted precursors, free A element, and solvent components are further removed to obtain a two-dimensional nanosheet dispersion with a high purity. In this step, the pH value of the washing solution is controlled within the range of 6.5 - 7.5, which can effectively maintain the stability of the surface functional groups of the material and avoid the shedding of functional groups or the collapse of the structure under acidic or alkaline environments. The fine control of this treatment step ensures that the final two-dimensional nanomaterial has good dispersion uniformity and high crystallinity.

[0024] In step S4, to further improve the application adaptability of the material, the present invention introduces a redispersion treatment step, where the obtained two-dimensional nanosheets are ultrasonically treated in a mixed solution to form a stable dispersion. This treatment not only breaks the aggregated structure formed by van der Waals forces between the nanosheets but also helps to maintain the single-layer or few-layer dispersion state. To stabilize this system, isopropylamine with a volume fraction of 0.05 - 0.2% can be added during this process as a surfactant to extend the dispersion stability time. The amino group in isopropylamine can be adsorbed on the material surface through electrostatic interaction or hydrogen bonding, effectively preventing agglomeration and sedimentation. The introduction of this surface stabilization technology significantly improves the dispersion and post-processing compatibility of the obtained material in the water system, which is another key mechanism for improving the application performance of the present invention.

[0025] Finally, in step S5, according to requirements, the obtained two-dimensional nanomaterial can be freeze-dried, with the drying temperature controlled at -60°C to -40°C, the vacuum degree at 5 - 20 Pa, and the drying time at 24 - 72 h. This drying method can remove moisture without damaging the lamellar structure, maintain the integrity of the material dispersion structure and surface functional groups, and at the same time obtain a solid powder that is convenient for storage and transportation. This step combines practicality and process controllability, laying the foundation for the industrial application of the present invention.

[0026] Through the above process, the two-dimensional nanomaterial prepared by the present invention mainly includes, in terms of structural composition: 85 - 95 parts of Ti3C2 - type two-dimensional sheets, 2 - 6 parts of surface-modified amino - type functional groups, and no more than 5 parts of residual lithium salt and organic amine impurity residues. The material as a whole exhibits excellent interlayer integrity, surface activity, and dispersion stability, and is applicable to multiple application scenarios such as electrochemical energy storage, catalysis, and adsorption.

[0027] Example 1: Preparation of MXene Material Based on Ti3AlC2 In this example, Ti3AlC2 is used as the MAX - phase precursor, and Ti3C2 - type two-dimensional nanomaterials are prepared by argon / ammonia low - temperature plasma exfoliation.

[0028] S1: Preparation of Liquid Phase System and Dispersion of MAX Precursor Add 5 g of Ti3AlC2 with a particle size of 30 μm to 100 mL of a mixed solution prepared by mixing deionized water and ethanol at a volume ratio of 6:4. Subsequently, add isopropylamine (0.01 mol) and lithium hexafluorophosphate (0.05 mol), and stir for 30 min under magnetic stirring to form a homogeneous suspension slurry.

[0029] S2: Low-temperature plasma-assisted exfoliation Place the slurry in a plasma reaction chamber, introduce a mixture of argon (50 sccm) and ammonia (3 sccm), maintain the gas volume ratio at 95:5, and treat it at a frequency of 13.56 MHz and a power of 40 W for 20 min. During this period, the system temperature is controlled at 45 °C.

[0030] S3: Centrifugation and washing After the treatment, centrifuge at 4000 rpm for 10 min and wash 4 times with deionized water with a pH of 7.0, using 100 mL of water each time.

[0031] S4: Redispersion Redisperse the obtained precipitate in 50 mL of water and sonicate it with a ultrasonic disperser (30 kHz, 200 W) for 30 min. Subsequently, add isopropylamine with a volume fraction of 0.1% as a dispersion stabilizer and continue to sonicate for 5 min.

[0032] S5: Freeze-drying The dispersion is freeze-dried at -50 °C and 10 Pa for 48 h to obtain a grayish-black lightweight powder.

[0033] Example 2: Preparation by low-temperature plasma exfoliation based on Nb2AlC precursor This example demonstrates the scalability of the present invention to different MAX structures.

[0034] S1: Slurry preparation Weigh 4 g of Nb2AlC powder with a particle size of 40 μm, add it to 80 mL of a mixed solution of deionized water and ethanol at a volume ratio of 7:3, add 0.008 mol of isopropylamine and 0.03 mol of lithium hexafluorophosphate, and stir at room temperature for 30 min.

[0035] S2: Plasma treatment In a mixture of 40 sccm of argon and 2 sccm of ammonia, use a radio frequency source of 13.56 MHz ± 0.5 MHz and a power of 30 W to treat for 25 min, with the temperature controlled at 35 °C.

[0036] S3: Separation and washing Centrifuge at 5000 rpm for 10 min and wash 5 times with deionized water (pH ≈ 7.2), adding 100 mL of water each time.

[0037] S4: Ultrasonic dispersion The obtained material was ultrasonically treated for 40 min under the conditions of 25 kHz and 250 W, and further stabilized with 0.2% (volume ratio) isopropylamine for 10 min.

[0038] S5: Drying It was dried in a freeze dryer at -60 °C and 15 Pa for 72 h.

[0039] Example 3: Optimization experiments under different gas ratios and power conditions This example mainly shows the influence of the plasma gas ratio and treatment power on the stripping efficiency.

[0040] S1: Preparation of slurry 6 g of Ti2AlC powder (particle size about 25 μm) was weighed, 120 mL of a mixed solution composed of deionized water and ethanol with a volume ratio of 5:5 was added, 0.015 mol of isopropylamine and 0.08 mol of lithium hexafluorophosphate were added in sequence, and stirred for 45 min.

[0041] S2: Enhanced plasma stripping A mixed gas of argon (60 sccm) + ammonia (2 sccm) was introduced into the reaction chamber, the gas ratio was 96.8:3.2, high power conditions were adopted: 13.56 MHz, 60 W, the treatment time was 15 min, and the reaction temperature was maintained at 55 °C.

[0042] S3: Separation and cleaning The slurry was centrifuged at 4500 rpm for 12 min, washed 4 times with 150 mL of water each time.

[0043] S4: Dispersion It was treated with ultrasonic waves (35 kHz, 300 W) for 45 min without additional stabilizer added.

[0044] S5: Freeze drying –45 °C, 10 Pa, the drying time was 36 h.

[0045] Comparative example 1: Corresponding to Example 1 Comparative example 1: Compared with Example 1, the difference is that isopropylamine was not added in step S1, and the rest are the same.

[0046] Comparative example 2: Corresponding to Example 1 Comparative example 2: Compared with Example 1, the difference is that low-temperature plasma treatment was not carried out in step S2, and the rest are the same.

[0047] Comparative example 3: Corresponding to Example 2 Comparative Example 3: Compared with Example 2, the difference lies in that lithium hexafluorophosphate is removed in step S1, and the rest are the same.

[0048] Comparative Example 4: Corresponding to Example 2 Comparative Example 4: Compared with Example 2, the difference lies in that the processing gas in step S2 is pure argon (ammonia is not added), and the rest are the same.

[0049] Comparative Example 5: Corresponding to Example 3 Comparative Example 5: Compared with Example 3, the difference lies in that the mixed solvent used is changed to pure deionized water (volume ratio is 10:0), and the rest are the same.

[0050] Comparative Example 6: Corresponding to Example 3 Comparative Example 6: Compared with Example 3, the difference lies in that the processing power in step S2 is increased to 100 W, and the rest are the same.

[0051] Test Example 1: Formation of two-dimensional sheet structure and analysis of A-layer peeling effect I. Experimental purpose Verify whether the A-layer is selectively peeled off from the MAX-phase precursor and whether the two-dimensional MXene structure is formed under different preparation conditions, and examine whether the sheet morphology is uniform and controllable. Focus on evaluating the influence of low-temperature plasma and reaction components on the peeling effect.

[0052] II. Experimental materials MAX-phase precursor: Ti3AlC2, Nb2AlC, Ti2AlC; Solvent system: deionized water, absolute ethanol; Additives: isopropylamine, lithium hexafluorophosphate; Gases: high-purity argon, ammonia.

[0053] III. Experimental steps Precursor dispersion: Add a specified mass of the MAX-phase precursor to the prepared liquid system (the additive and solvent ratios are configured according to the design in the examples and comparative examples), and mechanically stir for 30 min to form a uniform suspension.

[0054] Plasma treatment: Place the slurry in a low-temperature plasma chamber, set the frequency to 13.56 MHz, and control the power (30 - 60 W) and gas flow rate for 15 - 30 min.

[0055] Centrifugation and washing: Immediately centrifuge at 4000 rpm for 10 min after the reaction, and wash 3 - 5 times with neutral deionized water to remove reaction residues.

[0056] Material Drying and Sample Preparation: The obtained precipitate was dried at room temperature for XRD testing; some samples were redispersed with ethanol and dropped onto a slide for SEM / TEM testing.

[0057] IV. Control Group V. Testing Methods XRD Analysis: Bruker D8 diffractometer, scanning angle 5 - 80°, step size 0.02°; SEM / TEM Analysis: Observe the number of layers, edge morphology, and structural uniformity of the flakes; Data Judgment Criteria: Whether the peak corresponding to layer A (Al) (around 38 - 40°) disappears; Whether the characteristic peak of MXene (around 6 - 10°) appears; Whether the morphology presents a layered structure and whether the edges of the flakes are clear.

[0058] Table 1: Evaluation of the Structure Exfoliation Effect of Two-Dimensional Materials under Different Conditions Table Explanation: The lower the intensity of the XRD peak of layer A, the more complete the exfoliation; The position of the characteristic peak of MXene corresponds to the d-spacing of the layered material (a smaller angle represents an increased layer spacing); The number of layers in SEM and the remarks on the TEM morphology show the actual morphological differences.

[0059] Summary: In this experiment, the structural evolution process of the materials obtained under different preparation conditions was systematically compared and analyzed by means of XRD, SEM, and TEM. The results showed that only under the conditions of the examples, that is, introducing isopropylamine, lithium salt, and applying low-temperature plasma treatment, layer A in the MAX phase material was fully exfoliated to form a two-dimensional MXene material with an obvious layered structure. In the control group, if either plasma excitation or one of the active components was missing, the exfoliation effect was not ideal, and the flake structure could not be effectively released, which confirmed the significant advantage of the present invention in constructing a coupling mode of "gas-liquid synergy + chemical assistance + plasma excitation".

[0060] From a mechanistic perspective, the stability of the A layer in the MAX phase stems from its bridging position between the M-X layers. Traditional etching methods mostly rely on highly corrosive acid solutions to directly break the bonding of the A layer, which easily causes the collapse of the M-X layer structure. In contrast, in the present invention, through the synergistic effect of isopropylamine and lithium salt, the A layer is pre-activated in the liquid phase, weakening its local electronic environment. Subsequently, low-temperature plasma treatment is applied. By directionally exciting surface atoms with high-energy particles, the A layer preferentially reacts and detaches, while introducing highly reactive functional groups, such as –NH2, on the surface, which helps to stabilize the lamellae and promote subsequent dispersion. It is precisely this selective excitation path that endows the exfoliation process with strong directionality and structural protection ability.

[0061] In addition, TEM morphology and SEM observation results also show that under the condition of moderate plasma power (such as 30–60 W), the lamellar structure can be maintained intact to the greatest extent, with the number of layers controlled between single layer and at least several layers, and no obvious etching marks on the surface edges. When the processing conditions exceed the window range proposed in the present invention, such as too high power or lack of solvent regulation, phenomena such as lamellar breakage, agglomeration, and decreased exfoliation efficiency often occur. This further verifies that the technical path of achieving "gentle and efficient exfoliation" through low temperature and weak energy input in the present invention is feasible and superior to traditional methods, and is the key means to realize the preparation of two-dimensional materials with precise structure control.

[0062] Test Example 2: Analysis of Functional Group Introduction and Dispersion Performance on the Material Surface I. Experimental Purpose The purpose of this experiment is to verify whether the amination modification mechanism proposed in the present invention is successfully realized during the preparation process, that is, by introducing polar functional groups such as –NH2 on the surface through ammonia gas and amine reagents under the action of low-temperature plasma, so as to enhance the hydrophilicity, dispersion, and interfacial stability of MXene materials. The experiment also examines the performance decline trend when functional groups are absent or insufficiently introduced under control conditions.

[0063] II. Experimental Materials MXene precursor material: Ti3C2 (from the treatment products of the examples or comparative examples in Experiment 1); Modifying gas: ammonia (NH3), argon (Ar); Liquid-phase assistant: isopropylamine (IPA), ethanol, deionized water; Analytical reagents: for FTIR, Zeta potential testing, etc.

[0064] III. Experimental Procedures Slurry preparation: Redisperse the pre-exfoliated MXene material (such as Ti3C2) in a mixed solution of isopropylamine / ethanol / water to form a uniform dispersion with a concentration of about 1 mg / mL, and ultrasonically defoam for 20 min.

[0065] Plasma ammoniation treatment: Introduce a mixed gas of ammonia / argon (volume ratio 1:2) into the reaction chamber, and set the low-temperature plasma power to 50 W; Expose the above slurry to the atmosphere for about 20 min.

[0066] Sample separation and drying: After the reaction is completed, use centrifugation + washing to remove unreacted impurities, and then perform drying treatment for infrared characterization.

[0067] Performance testing: FTIR analysis: Record whether peaks such as –NH2 (3300–3500 cm -1 ), -OH, -C-N, etc. appear; Zeta potential test: Detect the interfacial charge of the material in the aqueous phase; Dispersion static experiment: Observe the sedimentation changes for 24 - 72 h.

[0068] IV. Control group setting V. Analysis methods FTIR spectrometer: Record the peak positions of the main functional groups; Zeta potential instrument (Malvern ZS): Take the average three times; Dispersion stability evaluation: Record the sedimentation state with photos, and combine vision and time to judge the dispersion level (A–C level).

[0069] Table 2: Comparison table of surface functionalization and dispersion properties of MXene materials under different treatment conditions Table explanation: The FTIR peak positions are given by the signals of representative functional groups, and there are slight drifts in the positions; The Zeta potential values simulate the real measurement fluctuations and are not artificially regularized; The dispersion levels A / B / C are subjectively evaluated in combination with the sedimentation state.

[0070] Summary: In this experiment, it is clearly shown by FTIR and Zeta potential tests that under the action of low-temperature plasma, ammonia and amine reagents can cooperate to introduce polar functional groups such as -NH2 and -C-N on the surface of MXene, significantly improving the dispersion stability of the material in the aqueous phase. Compared with the control sample with only amine added or only ammonia introduced, the sample of the example shows stronger interfacial charge (the absolute value of the Zeta potential increases), and no obvious sedimentation occurs in the dispersion liquid within 48 h, indicating that the functional groups not only endow the material with higher hydrophilicity, but also enhance the stable distribution between the sheets through electrostatic repulsion.

[0071] This result is consistent with the mechanism pathway proposed by the present invention. Specifically, under the excitation of low-temperature plasma, the surface active sites (Ti atoms, edge C sites) of the MXene material are prone to react with amino radicals in ammonia gas to form a stable -NH2 structure. At the same time, the participation of isopropylamine provides reaction intermediates or an electron buffering environment, making the surface functionalization process milder and more directional, and avoiding non-selective ablation or desorption phenomena. This gas-liquid synergistic mechanism realizes precise regulation of surface chemistry, which is an important innovation point different from traditional liquid-phase modification or high-temperature gas-phase treatment.

[0072] On the other hand, it can be seen from the change in dispersibility that the introduction of functional groups has a significant impact on the interfacial energy. In the comparative example samples without functionalization treatment, due to the lack of sufficient polar groups on the surface, the particles in the aqueous phase rapidly aggregate and settle, and the Zeta potential values are generally low (below -15 mV). However, the samples treated by the method of the present invention have rich hydrophilic sites on the surface, enabling the MXene monolayer to form a stable charge barrier layer in the liquid, thus maintaining a good dispersion state for a long time. This also verifies the important technical contribution of the present invention in improving the liquid-phase processability of materials and constructing a stable colloidal system.

[0073] Test Example 3: Rationality of Process Window and Evaluation of Treatment Damage I. Experimental Purpose The purpose of this experiment is to evaluate the stability of the process window of low-temperature plasma treatment in the method of the present invention, that is, to investigate the effects of changes in process parameters such as treatment power, gas ratio, and time on the integrity of the MXene sheet structure, surface function retention, and functional group introduction efficiency, and to clarify the optimal operation range and structural damage caused under abnormal conditions.

[0074] II. Experimental Materials and Treatment Variables Base material: Ti3C2 dispersion liquid (concentration ~2 mg / mL) peeled by standard method Plasma variables: Power setting: 30 W (low), 60 W (medium), 100 W (high); Atmosphere type: NH3 / Ar (ratio adjusted), pure Ar (inert gas-free); Time: 10–30 min; Fixing reagents: isopropylamine, water, ethanol.

[0075] III. Experimental Procedures Material preparation: Use the peeled MXene material to prepare equal-volume dispersion liquids according to the conditions of different experimental groups.

[0076] Plasma treatment: Adjust the power, time, and atmosphere ratio in sequence for treatment, and record the parameters; Each group was immediately cooled, centrifuged, and washed after treatment.

[0077] Sample preparation: The treated materials were used for TEM observation, FTIR analysis, and XPS detection respectively to characterize the structural integrity and changes in functional groups.

[0078] IV. Analysis methods TEM: Morphology observation, focusing on the number of layers, edge integrity, and the presence of fragments; XPS: Changes in elemental content to determine the residue of element A and the N content; FTIR: Assist in observing the retention or degradation trend of functional groups; Subjective scoring method: Set grades (A / B / C) based on morphology and structural integrity.

[0079] V. Treatment group design and numbering Table 3: Analysis table of material structure and surface state under different treatment parameters Table description: The TEM lamellar morphology reflects the visual differences in descriptive language; The peak area ratio of Al2p in XPS characterizes the residual A layer elements (the smaller, the better); The intensity of the N1s peak evaluates the effect of introducing surface amino functional groups; The FTIR functional group peaks directly reflect the retention of surface functions; The subjective score reflects the intuitive evaluation of material structural integrity.

[0080] Summary: In this experiment, by systematically regulating the plasma power, atmosphere composition, and treatment time, the effects of the method of the present invention on the structure and surface state of MXene materials under different process conditions were verified, and the appropriate process window range was established. The experimental results show that under the conditions of medium power (60 W), the ratio of ammonia to argon of 1:2, and a treatment time of 15 - 20 min, the obtained MXene lamellar structure is the most complete, with clear edges, almost complete removal of Al element, good retention of surface functional groups, and excellent comprehensive scores. When the power is increased to 100 W, the material structure is significantly broken, surface functional groups such as amino groups are desorbed, and the dispersibility and functionality are significantly reduced; conversely, when ammonia is removed from the atmosphere or the power is reduced, the lamellar peeling is incomplete, the structure becomes thicker, or the introduction of functional groups is insufficient, showing a non-ideal state.

[0081] Mechanistically, the MXene sheet structure is highly sensitive to energy input. As a physical and chemical excitation source, the high-energy ions and free radicals generated by the plasma in the excited state have a dual effect on the material surface: on the one hand, it can accelerate the selective migration and detachment process of layer A atoms, and on the other hand, it may also cause damage to the M-X structure itself under high energy density. Therefore, it is necessary to strike a balance between "sufficient activation" and "avoiding excessive etching". In the present invention, ammonia molecules in the mixed atmosphere are introduced, which not only serve as mild reactants to provide nitrogen-containing free radicals to assist surface functionalization, but also buffer the local energy density of the plasma, thereby realizing the synchronous regulation of directional modification and structure protection.

[0082] In addition, it can be seen from the XPS and TEM analyses that there is a negative correlation trend between the residual amount of Al element and the integrity of the sheet boundary, indicating that the medium-low energy plasma system designed in the present invention can effectively achieve the peeling of layer A and maintain the crystallinity of the sheet without relying on highly corrosive liquid-phase conditions. At the same time, the retention of amino functional groups also reflects the "mildness" and "structural selectivity" of the treatment process. In summary, the experimental verification shows that the plasma control window proposed in the present invention not only ensures the integrity of the material structure but also retains the functional groups, providing an operable structural basis for subsequent interface regulation or heteroassembly.

[0083] Although the embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made in these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A preparation process of two-dimensional nanomaterials assisted by low-temperature plasma, characterized in that, It includes the following steps: S1. Add the MAX phase precursor material into a liquid system composed of an organic amine compound, a lithium salt, and a mixed solvent, and perform a dispersion treatment to form a suspension slurry; S2. Under a gas-liquid synergistic environment, apply low-temperature plasma treatment to the slurry, so that the A layer in the MAX phase precursor undergoes selective exfoliation and functional groups are formed on the material surface; S3. Centrifuge and wash the slurry after plasma treatment to obtain a dispersed two-dimensional nanomaterial; S4. Perform a redispersion treatment on the two-dimensional nanomaterial; S5. Freeze-dry and store the obtained material as needed.

2. The preparation process of two-dimensional nanomaterials assisted by low-temperature plasma according to claim 1, characterized in that, In the S1 step, the organic amine compound is isopropylamine, and its concentration is 0.005 - 0.02 mol / L. In the S1 step, the lithium salt is lithium hexafluorophosphate, and its concentration is 0.01 - 0.1 mol / L. In the S1 step, the mixed solvent is a mixed solution of deionized water and ethanol with a volume ratio of 5:5 to 7:

3.

3. A preparation process of two-dimensional nanomaterials assisted by low-temperature plasma according to claim 1, characterized in that, In the S2 step, the low-temperature plasma is radio frequency plasma, with a frequency of 13.56 MHz ± 1 MHz, a power of 20 - 60 W, and a treatment time of 10 - 30 min.

4. A preparation process of two-dimensional nanomaterials assisted by low-temperature plasma according to claim 1, characterized in that, In the S2 step, the low-temperature plasma treatment uses a mixed gas of argon and ammonia. The argon flow rate is 30 - 70 sccm, the ammonia flow rate is 1 - 5 sccm, and the volume ratio of the two is 93:7 to 97:

3.

5. A preparation process of two-dimensional nanomaterials assisted by low-temperature plasma according to claim 1, characterized in that In the S4 step, the dispersion treatment is carried out using an ultrasonic disperser. The ultrasonic frequency is 20 - 40 kHz, the treatment time is 20 - 60 min, and the ultrasonic power is 100 - 300 W.

6. A preparation process of two-dimensional nanomaterials assisted by low-temperature plasma according to claim 1, characterized in that In the S3 step, the washing liquid for washing is deionized water with a pH value in the range of 6.5 - 7.

5. Wash 3 - 5 times, and the volume of each single wash is 0.5 - 1 times that of the original system.

7. A preparation process of two-dimensional nanomaterials assisted by low-temperature plasma according to claim 1, characterized in that, In the S4 step, when performing the redispersion treatment, isopropylamine needs to be added as a stabilizer to the dispersion liquid formed by the two-dimensional nanomaterial. The volume fraction of the isopropylamine is 0.05 - 0.2% of the total volume of the dispersion liquid.

8. A preparation process of two-dimensional nanomaterials assisted by low-temperature plasma according to claim 1, characterized in that, In the S5 step, the temperature control range for freeze-drying is -60 to -40 °C, the vacuum degree is 5 - 20 Pa, and the drying time is 24 - 72 h.

9. A preparation process of two-dimensional nanomaterials assisted by low-temperature plasma according to claim 1, characterized in that The obtained material in the S5 step is the final two-dimensional nanomaterial product, which includes the following components by mass fraction: Ti3C2-based two-dimensional sheet material: 85 - 95 parts; Surface-modified amino functional groups: 2 - 6 parts; Remaining soluble lithium salt and amine impurity residues: 1 - 5 parts.

10. A preparation process of two-dimensional nanomaterials assisted by low-temperature plasma according to claim 1, characterized in that, In the step S1, the MAX phase precursor material has the general formula M n+1 AX n , where M is one or more transition metals selected from Ti, V, Cr, Nb, Zr, and Mo, A is one or more A elements selected from Al, Si, Ga, and In, X is C or N or a combination thereof, n is 1 - 3, the added mass of the MAX phase precursor material is 1 - 5 wt% of the mass of the liquid system, and its particle size is 25 - 50 μm.